PARTICIPATORY ADMINISTRATIONS OF EDUCATIONAL PARTNERSHIPS AFFECTING THE DEVELOPMENT OF ACADAMIC EXCELLENCE IN PRIVATE SCHOOLS UNDER CHONBURI PROVINCIAL EDUCATION OFFICE - Suknana, Rachawadee; Warabamrungkul, Theerangkoon; Nilkote, Reongwit (Journal of MCU Nakhondhat, 2024)
This research aimed to: 1) Study participative management of educational stakeholders under the Chonburi Provincial Education Office, 2) Examine the development towards excellence of private educational institutions under the Chonburi Provincial Education Office, 3) Investigate the relationship between participative management of educational stakeholders and the development towards excellence of private educational institutions under the Chonburi Provincial Education Office, and 4) Create a predictive model for participative management of educational stakeholders that impacts the development towards excellence of private educational institutions under the Chonburi Provincial Education Office. This quantitative research utilized questionnaires with a sample group of 357 administrator and teacher under Chonburi provincial education office. The sample size was determined using Krejcie and Morgan’s sample size table. Data analysis included means, standard deviations, Pearson’s correlation coefficients, and simple regression analysis. The findings indicated that: 1) Education partnerships participatory management was rated highest ( = 4.55, S.D. = 0.47), 2) Development towards excellence of private schools was also rated highest ( = 4.58, S.D. = 0.4), 3) There was a significant positive correlation between participatory management and development towards excellence of private schools at the .01 level, and 4) Participatory management affecting the development towards excellence of private schools was established predictive equation for development towards excellence of private schools it was possible to create forecast equations with 69 %. The predictive equations were formulated as follows: Raw score prediction = 1.086 + 0.769X and Standardized score prediction = 0.83*Zx.